1960
DOI: 10.1111/j.1748-1716.1960.tb01879.x
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Muscular Work

Abstract: ASTRAND, I., P.-0. ASTRAND, E. H. CHRISTENSEN and R. HEDMAK. Intermittent muscular work. Acta physiol. scand. 1960. 48. 448-453. -The physiological effect of rest pauses on a non-steady state work (2,160 kpm/min) was studied. A physically well trained subject performed in one hour a total amount of 64,800 kpm on a bicycle ergometer by intermittent work with 0.5, 1, 2 or 3 min periods of work and rest. Total 0, intake, total pulmonary ventilation, total number of heart beats and blood lactic acid concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
107
1
17

Year Published

1971
1971
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(140 citation statements)
references
References 3 publications
15
107
1
17
Order By: Relevance
“…Studies in healthy people have shown that repeated maximal-intensity exercise bouts, allowing corresponding short rest intervals between bouts, can be tolerated for an extensive period [7] and yield similar physiological benefits to extended high-intensity continuous exercise [22,23]. Furthermore, as shown in healthy individuals [24], the metabolic response to interval exercise is very similar to that to continuous exercise at half the WR, suggesting that the relief intervals between bouts of hard work in IT bear special importance with regard to the successful application of maximal-intensity training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in healthy people have shown that repeated maximal-intensity exercise bouts, allowing corresponding short rest intervals between bouts, can be tolerated for an extensive period [7] and yield similar physiological benefits to extended high-intensity continuous exercise [22,23]. Furthermore, as shown in healthy individuals [24], the metabolic response to interval exercise is very similar to that to continuous exercise at half the WR, suggesting that the relief intervals between bouts of hard work in IT bear special importance with regard to the successful application of maximal-intensity training.…”
Section: Discussionmentioning
confidence: 99%
“…repeated periods of maximal or high-intensity exercise alternating with corresponding short intervals of rest. Early studies in healthy subjects showed that more work can be performed before exhaustion sets in by exercising with intervals than when the same total amount of work is performed continuously [7][8][9]. GOSSELINK et al [10] and COPPOOLSE et al [11] examined the effects of IT on measures of exercise tolerance and compared its efficacy to that of continuous exercise in COPD patients.…”
mentioning
confidence: 99%
“…This is important because longer periods of hyperoxia are accompanied by reductions in resting MSNA and BP as a result of chemoreflex inhibition (8,26,38). Moreover, isometric exercise produces a greater increase in BL than rhythmic exercise (5,36).…”
mentioning
confidence: 99%
“…ndurance training effects of short-duration intermittent runs have been reported in athletes (3,9,23) with improved maximal oxygen consumption ( _ Vo 2 max) and delayed fatigue compared to continuous running methods (10,15). Balsom et al (5,8) have shown that short-duration intermittent training allows limited lactate production and increased creatine phosphate metabolism during intermittent exercise.…”
mentioning
confidence: 99%